2019
DOI: 10.1097/scs.0000000000005136
|View full text |Cite
|
Sign up to set email alerts
|

Management of Craniopharyngioma

Abstract: Objective: Craniopharyngiomas are one of the most challenging problems for neurosurgeons because of the high recurrence rates due to their localization and associated endocrinological disorders. This study reports the outcomes of surgeries and recurrence rates of 45 craniopharyngioma cases. Method: Patients who were diagnosed with craniopharyngioma in the authors’ clinic between 1998 and 2016 evaluated retrospectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In our cohort, there were more male patients (n = 187, 55.82%) than female patients (n = 148, 44.18%), consistent with previous reports ( 29 31 ). Although CPs were more common among child patients, the proportion of adult patients was higher in this study (84.78 vs. 15.22%); because adult patients were the main group of patients in our ward.…”
Section: Discussionsupporting
confidence: 92%
“…In our cohort, there were more male patients (n = 187, 55.82%) than female patients (n = 148, 44.18%), consistent with previous reports ( 29 31 ). Although CPs were more common among child patients, the proportion of adult patients was higher in this study (84.78 vs. 15.22%); because adult patients were the main group of patients in our ward.…”
Section: Discussionsupporting
confidence: 92%
“…Craniopharyngiomas are histologically benign neuroepithelial tumors of the central nervous system (CNS) with malignant behavior, which are predominantly observed in children aged 5 to 10 years. These lesions tend to invade surrounding structures and to recur after a total resection (13,14). Two of 4 craniopharyngiomas in this study showed a recurrence during the follow-up period, and reoperation was needed.…”
Section: A B Cmentioning
confidence: 65%
“…At the same time, the results also showed that ACP involved the hypothalamus to varying degrees, and even in tissue specimens from the same patient, there were significant differences in the degree of tumour involvement of the hypothalamus in different regions (Figure S2a–c). It has been previously reported that the finger‐like protrusions of ACP appear to be related with the recurrence [3, 22–24]. Therefore, the finger‐like protrusions of ACP could be an important factor in tumour recurrence.…”
Section: Resultsmentioning
confidence: 96%
“…ACP accounts for nearly 90% of CP cases, and its management remains one of the most challenging issues for neurosurgeons. Although it is histologically benign, ACP usually infiltrates the adjacent structures, such as the pituitary, hypothalamus, optic nerves, vascular structures and the third ventricle, often making a complete surgical resection difficult or even unfeasible [3]. Despite resection with or without radiotherapy, the rate of recurrence remains relatively high ($25%) [4,5].…”
Section: Introductionmentioning
confidence: 99%